Desain Pembelajaran Blended: Memfasilitasi Praktek Mengajar Mahasiswa Calon Guru - Nurrijal, Nurrijal (Jurnal Biologi Babasal, 2023)
Abstract : Higher education institutions must prioritize achieving graduate learning outcomes to produce excellent and competent graduates. Innovations in nurturing experienced prospective teachers in the field of education need to be directed towards creating professional teachers. Faculty members need to develop teacher education programs through consecutive approaches that integrate subject matter knowledge and pedagogical knowledge. In the era of the Fourth Industrial Revolution, education faces new learning challenges that prioritize data, technology, and human literacy. Faculty members must innovate learning to adopt these new literacies. The Fourth Industrial Revolution requires changes in managing prospective teacher students, particularly in independent learning mastery, problem-solving, and utilization of digital learning resources. Blended learning is an innovative learning model that can address these challenges. Through a combination of innovative learning and blended learning system patterns, students can learn flexibly and effectively. The outcome of this research is a pedagogical learning model that can be implemented by higher education institutions to enhance teacher education quality. This research applies the Research and Development (R&D) method, implementing several stages including Analysis, Design, Development, Implementation, and Evaluation. The research findings show the development of a blended learning-based learning design that is valid and practical, categorized as excellent, and effectively enhances independent constructivism by 92% and guided constructivism by 85%, as well as independent social constructivism by 91% and guided social constructivism by 80%. Based on the research results, it can be concluded that this learning design is deemed suitable for promoting the constructivism and social constructivism abilities of prospective teacher students.